APPLICATION OF E-GOVERNMENT IN IMMIGRATION MANAGEMENT INFORMATION SYSTEM (SIMKIM) AT DIRECTORATE GENERAL OF IMMIGRATION - YUSUF RIZKY ADITYA (Polteknik Imigrasi, 2020)
The government is currently implementing an e-government system to provide services to the community using technology. E-government or electronic government is the use of information technology by the government to provide information and services to its citizens. Presidential Instruction No. 3 of 2003 concerning national policies and strategies for e-government development and Presidential Regulation of the Republic of Indonesia Number 95 of 2018 concerning Electronic-Based Government Systems are the legal basis for designing SPBE in Indonesia. The application of e-government at the Directorate General of Immigration can be seen in its centralized services using SIMKIM. This research uses a qualitative approach with descriptive analysis method. In the discussion this research has been based on the selection of research problems related to the suitability of e-government design in SIMKIM at the Directorate General of Immigration based on Presidential Instruction No. 3 of 2003 and Presidential Decree No. 95 of 2018 and the implementation of e-government at the Directorate General of Immigration according to the stages of the Deloitte and Touche framework. The results of the discussion stated that the implementation of e-government at the Directorate General of Immigration was in accordance with the two regulations and the Director General had entered the second stage based on the Deloitte and Touche framework. It is hoped that this research can be used for further research development.